PEMBELAJARAN ARIAS DENGAN SETTING KOOPERATIF DALAM PEMBELAJARAN GEOMETRI ANALITIK BIDANG - Sulistyaningsih, Murni; Mangelep, Navel Oktaviandy (Jurnal Pendidikan Matematika (JUPITEK), 2019)
The purpose of this study is to know the improvement in student learning outcomes taught through ARIAS learning with cooperative settings in learning Analytical Geometry Fields. This study uses a research design type 0ne-Shot Case Study. The research subjects were lecturers and students of the second semester of the Department of Mathematics Education Unima, academic year 2018/2019, which succeeded 25 students. Data obtained through the results of the test form description. Obtained the average results of student learning outcomes using this learning model is 82 with a maximum value of 95, while the results of inferential statistical analysis obtained results t_hitung= 12,3494 > t_tabel=1,708, with a real level (âˆ) = 0.05. This means the average learning outcomes are more than 62.5 which is a benchmark of graduation. The results showed that using the ARIAS learning model with cooperative settings in learning Geometry Analytic Fields can improve student learning outcomes